Analisis Pengukuran Kinerja Investasi PT. Taspen (Persero) dengan Menggunakan Metode Economic Value Added - Karina Oktaviani; Dadan Rahadian (Universitas Kristen Maranatha, 2014)
Corporate performance measurement will indicate the condition of a company when running operational activities for a certain period. Economic Value Added (EVA) in this case is very relevant for measuring the value or values performance because EVA is a measure of economic value added resulting from theactivities of the company or enterprise management strategy. However, be a mistake when limiting EVA only to measure the performance of the company alone. EVA can be used as the implementation of a strategy that is associated with the main function of the company. The problem in this research is to try to evaluate the performance of investment PT TASPEN (Persero) with measurement of performance using Economic Value Added (EVA), which aims to get the composition of the investmentportfolio of financial assets PT TASPEN (Persero) which provide value-added for priority. The method used in this research is descriptive quantitative method. Used in this study is a secondary data such as data accounting, financial statements and annual report PT TASPEN (Persero). The results showed that, based on the value of Economic Value Added (EVA) PT TASPEN (Persero) advised to invest with established priority that is: (1) Bonds, (2) Stocks, (3) Mutual funds, (4) directinvestment and (5) deposits.Keywords: Economic Value Added, PT TASPEN (Persero), investment